Immortalising cadaveric brain dissection using application photogrammetry - Dearbhla P. Cullinane; Basil Lim; Denis S. Barry (Brain Structure and Function, 2026)
Cortical and deep brain topography are core components of undergraduate neuroanatomy teaching and neurosurgical training. Due to the technical challenges associated with dissecting and maintaining preserved brains, deep white matter preparations are often omitted from anatomy curricula. This reduced opportunity for tactile neuroanatomical exploration contributes to surface-level approaches to learning and is associated with poorer student outcomes including neurophobia. Photogrammetric technologies present a potential solution by offering alternate modes to learn neuroanatomy. However, these technologies often require advanced scanning and specialised resources. In this study, we present a novel approach using the Klingler dissection method to perform white matter dissections of a formalin-preserved cadaveric brain and create high-fidelity 3D models at each dissection step using a smartphone application. Lateral-to-medial and medial-to-lateral dissections were performed and high-quality 3D models were generated using Polycam. Scanning artefacts were edited in Blender, and the final models were hosted on SketchFab. A sample of models were quantitatively compared with a high-end photogrammetry pipeline and were found to maintain exceptional visual and structural fidelity. The preservation of neuroanatomical dissections in this manner has the potential to improve resource accessibility, enhance spatial understanding, and guide the development of low-cost transferrable teaching resources.

Prostaglandin A2 Interacts with Nurr1 and Ameliorates Behavioral Deficits in Parkinson’s Disease Fly Model - Sreekanth Rajan; Hui Ting Toh; Hong Ye; Ziyin Wang; Adeline Henry Basil; Tanvi Parnaik; Jun Yeob Yoo; Kah-Leong Lim; Ho Sup Yoon (NeuroMolecular Medicine, 2022)

Identification of PP2A and S6 Kinase as Modifiers of Leucine-Rich Repeat Kinase-Induced Neurotoxicity - Joan Poh Ling Sim; Wang Ziyin; Adeline Henry Basil; Shuping Lin; Zhongcan Chen; Chengwu Zhang; Li Zeng; Yu Cai; Kah-Leong Lim (NeuroMolecular Medicine, 2020)
Mutations in LRRK2 are currently recognized as the most common monogenetic cause of Parkinsonism. The elevation of kinase activity of LRRK2 that frequently accompanies its mutations is widely thought to contribute to its toxicity. Accordingly, many groups have developed LRRK2-specific kinase inhibitors as a potential therapeutic strategy. Given that protein phosphorylation is a reversible event, we sought to elucidate the phosphatase(s) that can reverse LRRK2-mediated phosphorylation, with the view that targeting this phosphatase(s) may similarly be beneficial. Using an unbiased RNAi phosphatase screen conducted in a Drosophila LRRK2 model, we identified PP2A as a genetic modulator of LRRK2-induced neurotoxicity. Further, we also identified ribosomal S6 kinase (S6K), a target of PP2A, as a novel regulator of LRRK2 function. Finally, we showed that modulation of PP2A or S6K activities ameliorates LRRK2-associated disease phenotype in Drosophila .

Untangling the dorsal diencephalic conduction system: a review of structure and function of the stria medullaris, habenula and fasciculus retroflexus - Elena Roman; Joshua Weininger; Basil Lim; Marin Roman; Denis Barry; Paul Tierney; Erik O’Hanlon; Kirk Levins; Veronica O’Keane; Darren Roddy (Brain Structure and Function, 2020)

Nutraceuticals in Parkinson’s Disease - Liting Hang; Adeline Henry Basil; Kah-Leong Lim (NeuroMolecular Medicine, 2016)